2014
DOI: 10.1007/s11139-013-9535-6
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Sato–Tate Vertical Distribution of the Satake Parameter of Maass Forms on PGL(N)

Abstract: We formulate a conjectured orthogonality relation between the Fourier coefficients of Maass forms on PGL(N). Based on the works of Goldfeld-Kontorovich and Blomer for N=3, and on our conjecture for N≥4, we prove a weighted vertical equidistribution theorem (with respect to the generalized Sato-Tate measure) for the Satake parameter of Maass forms at a finite prime. For N=3, the rate of convergence for the equidistribution theorem is obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…. , p kN−1 ) by the Casselman-Shalika formula (Proposition 5.1 of [Zho14]) and they are compatible with the Hecke relations. More explicitly, for a prime number p, we define A(p k1 , .…”
Section: Introductionmentioning
confidence: 62%
“…. , p kN−1 ) by the Casselman-Shalika formula (Proposition 5.1 of [Zho14]) and they are compatible with the Hecke relations. More explicitly, for a prime number p, we define A(p k1 , .…”
Section: Introductionmentioning
confidence: 62%
“…To conclude this section, we have shown that, for X ą 2p N´1 , we have 27) in the case of a form f which is not self-dual, and of odd N .…”
Section: Combinatorial Rearrangingmentioning
confidence: 92%
“…A well known fact about Dirichlet characters is the following orthogonality relation for integers m, n coprime to q, where the sum on the left is over all characters (mod q). Since Dirichlet characters can be viewed as automorphic representations of GL(1, A Q ), this result can be interpreted as the simplest case of the orthogonality relation conjectured by Zhou [19] concerning Fourier-Whittaker coefficients of Maass forms on the space SL n (Z)\SL n (R)/SO n (R), n ≥ 2. This orthogonality relation conjectured by Zhou was proved by Bruggeman [2] in the case n = 2 and by Goldfeld-Kontorovich [6] and Blomer [1] in the case n = 3.…”
Section: Introductionmentioning
confidence: 90%